Leadership and populism: A parallel reading of Hannah Arendt and Franz Neumann. (December 2019) - Sanders, Paul
Populism was the Cambridge Dictionary's new word of the year 2017. The surge in interest reflects recent events such as the UK Brexit referendum, the arrival of Donald Trump at the helm of the US presidency, or the electoral victories of self-styled anti-establishment leaders throughout Europe and the World. The first part of this article explores the scientific status of populism. It concludes that the widespread use of populism as a term obscures a number of epistemic and conceptual limitations, arguing that 'trouble-in-democracy' is the more pertinent and more penetrating lens. The configuration of this populism focus has consequences on the definition of populist leadership, which is dominated by the notion of charisma. Through engagement with Hannah Arendt and her fellow exile Franz Neumann the article proposes an alternative phenomenological framework for apprehending populist leadership. To do this, it relies on the analogies between populist and totalitarian leadership. Finally, it maps out the priority areas for the deployment of populist discourse and practice, arguing that this is where non-populist (responsible) leaders should be focusing their efforts.